2021
DOI: 10.5713/ajas.19.0926
|View full text |Cite
|
Sign up to set email alerts
|

The effect of seasonal thermal stress on milk production and milk compositions of Korean Holstein and Jersey cows

Abstract: Objective: In this study we investigated the effect of seasonal thermal stress on milk production and milk compositions between Holstein and Jersey dairy cows under the temperateclimate in Korea.Methods: A total of 9 Holstein lactating dairy cows (2.0±0.11 parity) which had a daily milk yield of 29.77±0.45 kg, and days in milk of 111.2±10.29 were selected similarly at the beginning of the experiments in each season. Also, a total of 9 Jersey lactating dairy cows (1.7±0.12 parity) which had a daily milk yield o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 21 publications
2
8
0
Order By: Relevance
“…We postulate, from these data, that milk composition was more susceptible to temperature than humidity in this study. In line with our results, Lim et al [ 52 ] stated that, in summer—when the average ambient temperature (°C) and temperature–humidity index (THI) were higher—there was a negative correlation between these factors and milk production, in addition to the proportions of milk fat and protein. This was explained by Johnson [ 53 ] as greater production of heat during summer speeding up the rate of decline in milk production for cows.…”
Section: Discussionsupporting
confidence: 92%
“…We postulate, from these data, that milk composition was more susceptible to temperature than humidity in this study. In line with our results, Lim et al [ 52 ] stated that, in summer—when the average ambient temperature (°C) and temperature–humidity index (THI) were higher—there was a negative correlation between these factors and milk production, in addition to the proportions of milk fat and protein. This was explained by Johnson [ 53 ] as greater production of heat during summer speeding up the rate of decline in milk production for cows.…”
Section: Discussionsupporting
confidence: 92%
“…Our study results are supported by Bohmanova et al [27] who reported that even with use of evaporative cooling, THI can't drop below 72, this may explain the sharp decline of milk production from June to August. Lim et al [28] reported that the greater heat production can explain the increasing rate of decline in milk yield for cows. Also, Bohmanova et al [27] showed milk production begins to recover from HS in October when THI was < 72.…”
Section: Resultsmentioning
confidence: 99%
“…Our study results are supported by Bohmanova et al [25] who reported that even with use of evaporative cooling, THI can't drop below 72, this may explain the sharp decline of milk production from June to August. Dong-Hyun Lim et al [26] reported that the greater heat production can explain the increasing rate of decline in milk yield for cows. Also, Bohmanova et al [25] showed milk production begins to recover from HS in October when THI was <72.…”
Section: Resultsmentioning
confidence: 99%